Decoupling from the West Will Be Hard on China’s Higher Education - Altbach, Philip; de Wit, Hans (International Higher Education, 2023)
China is engaged in a geopolitical conflict with the West, especially with the United States, and this has a significant impact on Chinese higher education. Collaborative research will decrease. China-funded Confucius Institutes have been closed. Within China itself, there are more restrictions on universities. Is a new “academic cold war” looming between China and the West?